DNA hypomethylation of Synapsin II CpG islands associates with increased gene expression in bipolar disorder and major depression. Issue 1 (December 2016) - Cruceanu, Cristiana; Kutsarova, Elena; Chen, Elizabeth; Checknita, David; Nagy, Corina; Lopez, Juan; Alda, Martin; Rouleau, Guy; Turecki, Gustavo
Abstract Background The Synapsins (SYN1, SYN2, andSYN3 ) are important players in the adult brain, given their involvement in synaptic transmission and plasticity, as well as in the developing brain through roles in axon outgrowth and synaptogenesis. We and others previously reported gene expression dysregulation, both as increases and decreases, of Synapsins in mood disorders, but little is known about the regulatory mechanisms leading to these differences. Thus, we proposed to study DNA methylation at theses genes' promoter regions, under the assumption that altered epigenetic marks at key regulatory sites would be the cause of gene expression changes and thus part of the mood disorder etiology. Methods We performed CpG methylation mapping focusing on the three genes' predicted CpG islands using the Sequenom EpiTYPER platform. DNA extracted from post-mortem brain tissue (BA10) from individuals who had lived with bipolar disorder (BD), major depressive disorder (MDD), as well as psychiatrically healthy individuals was used. Differences in methylation across all CpGs within a CpG island and between the three diagnostic groups were assessed by 2-way mixed model analyses of variance. Results We found no significant results forSYN1 orSYN3, but there was a significant group difference inSYN2 methylation, as well as an overall pattern of hypomethylation across the CpG island. Furthermore, we found a significant inverse correlation of DNA methylation withSYN2a mRNA expression. Conclusions These findings contribute to previous work showing dysregulation of Synapsins, particularlySYN2, in mood disorders and improve our understanding of the regulatory mechanisms that precipitate these changes likely leading to the BD or MDD phenotype.